Design and construction of patterned shells - Praveen Ravichandran (2014)
The performance of thin walled structures under compressive forces has been the focal point of many studies. Reducing the structure’s weight whilst maintaining its structural integrity is a key component in many of these studies. The increase in the specific internal energy of lighter materials leads to higher fuel efficiency, higher safety standards and is a more economically sound approach. The main aim of these project is to study how the energy absorption capabilities of structures differ with different geometries of holes embedded onto them. The structures’ material properties such as the Young’s modulus, the yield stress and the plastic hardening modulus are verified with the quasi-static tension tests. The structures, those with and without holes embedded onto them, are then submitted to lateral compression loads. With the aid of appropriate machines and software, the force displacement graphs are then plotted for these structures. The specific internal energy of these structures are calculated and comparisons are drawn. The specific internal energy of some of the lighter structures were found to be higher than that of the structure without any holes. The cause for the increase in the specific internal energy was found to be the different collapse model exhibited by these structures. All the structures embedded with holes which had higher specific internal energy than the structure without holes displayed the similar collapse model, the rectangular collapse model. The characteristics of the rectangular collapse model were found to be influenced by the dimensions and the orientations of the ellipse shaped holes. The specific internal energy of the structure was found to increase significantly when the major axes of the ellipse shaped holes were parallel the direction of the lateral compression force. However the formation of smaller areas should be avoided as they resulted in high stress concentrations. These increase in localised stresses caused the areas to be more susceptible to cracks and they decreased the specific internal energy drastically. The project was concluded with a recommendation of an optimum design of holes for the structure used in the experiments. As a roundup of the author’s project, recommendations for future works to include previously neglected parameters are discussed.